1999
DOI: 10.1097/00005053-199901000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Attachment Representation in Idiopathic Spasmodic Torticollis

Abstract: We investigated alexithymia and the mental representation of attachment in idiopathic spasmodic torticollis (IST). It was hypothesized a) that alexithymia in IST is more prevalent than in a nonclinical control group and b) that significant correlations emerge between alexithymia and a dismissing attachment representation. Twenty patients with IST and 20 healthy controls matched for age and sex were administered the Toronto Alexithymia Scale (TAS-20) and the Adult Attachment Interview (AAI). Attachment was clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 23 publications
6
28
0
2
Order By: Relevance
“…Also, attachment dimensions significantly improved the prediction of the TAS-20 score beyond that afforded by depression, anxiety, the Big Five factors, and temperament and character dimensions. Therefore, our results, as those of other recent studies [14,15,16], support an association between insecure attachment and alexithymia. Conceivably, this association is accounted for by the deep influence of early attachment experiences on the development of emotional and cognitive skills involved in affect regulation [37, 38].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, attachment dimensions significantly improved the prediction of the TAS-20 score beyond that afforded by depression, anxiety, the Big Five factors, and temperament and character dimensions. Therefore, our results, as those of other recent studies [14,15,16], support an association between insecure attachment and alexithymia. Conceivably, this association is accounted for by the deep influence of early attachment experiences on the development of emotional and cognitive skills involved in affect regulation [37, 38].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the association between attachment dimensions and the EOT subscale was less strong compared with the DIF and DDF subscales, while another study found opposite results [14]. That study used the Adult Attachment Interview Q-sort and was performed on patients with idiopathic spasmodic torticollis and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakdown in environmental communication may result in increased social isolation and subsequently decreased social support. There is evidence that alexithymia is associated with social anhedonia [48], nonverbal anger and interpersonally avoidant behavior [2], an avoidant/dismissive attachment style [49]and avoidance-oriented coping [41]. Because social support may be an important moderator between life stress and physical disease [50, 51, 52, 53, 54, 55], the link between stress-related disorders and alexithymia may be a breakdown in the ability to communicate with and utilize the emotional support of others.…”
Section: Discussionmentioning
confidence: 99%
“…Tendo em conta a importância dada pelas teorias da vinculação à regulação do afecto, vários estudos têm examinado esta relação (e.g., Scheidt et al, 1999;Troisi, D'Argenio, Peracchio, & Petti, 2001). Por exemplo, Troisi et al (2001) Deborde et al, 2012).…”
Section: Alexitimiaunclassified